The Possible Improving Effects of γ-Irradiated and/or Extruded Soy Flour on Hypercholesterolemic Rats - Refaat G. HAMZA; Safaa AFIFI; Abdel-Rahman B. ABDEL-GHAFFAR; Ibrahim H. BORAI (Notulae Scientia Biologicae, 2013)
Hypercholesterolemia is serious conditions that can cause fatal complications without careful management. Among the dietary supplementation with functional food, soybeans possess variety of antioxidant compounds that may lower incidence of hypercholesterolemia and degenerative cardiovascular disease. Thus, the purpose of this study is to determine the effect of gammairradiated and/or extruded soy flour on hypercholesterolemic rats. Processing of soy flour by γ-irradiation and/or extrusion reduced the amount of antinutritional factors such as tannin and trypsin inhibitor and resulted in different changes in the total amino acids and fatty acid contents. The animals maintained on the HCD showed remarkable decrease in the level of HDL-C associated with significant increase in the values of serum total lipid, total cholesterol, triglyceride, LDL-C, vLDL-C and the risk ratio in addition to serum concentration of urea, creatinine and uric acid in comparison with those of the control group. However, dietary supplementation of raw and treated soy flour resulted in reduction in the bad changes induced by HCD in the above mentioned parameters. In conclusion, treated soy flour supplementation in diet of rats pointed out to its hypocholesterolemic effect and its ability to improve lipid profile and kidney function of hypercholesterolemic rats.